The contribution of the private healthcare sector during the COVID-19 pandemic: the experience of the Lombardy Region in Northern Italy - Signorelli, Carlo; De Ponti, Emanuele; Mastrangelo, Marco; Pennisi, Flavia; Cereda, Danilo; Corti, Fiorenzo; Beretta, Dario; Pelissero, Gabriele (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Introduction. In Lombardy, the first European region hit by the COVID-19 pandemic, for decades the regional public healthcare service has followed a mixed delivery model with extensive involvement of private accredited providers. The study aimed at examining the role of the private sector in delivering healthcare services (diagnosis, hospitalization, and vaccination) during the pandemic. Study design. Healthcare system study Methods. We analysed regional healthcare data referring to the period from March 2020 onwards to assess the availability of acute care and intensive care hospital beds, SARS-CoV-2 tests, and COVID-19 vaccinations. We specifically examined healthcare offered by private accredited providers within the region. Results. Of the 12,306 converted beds for COVID-19 treatment, 4,975 (40%) were in accredited private hospitals. Intensive care beds increased by 95%, reaching 1,755, with 484 (28%) in accredited private hospitals. Since the pandemic onset, 28.9 million (62%) of SARS-CoV-2 tests were conducted by private accredited facilities including pharmacies. Private sector actively contributed to the COVID-19 vaccination campaign administering over 2.6 million doses in 2021, enhancing vaccination capacity to its peak. Conclusions. The longstanding relationship between the public and private sectors within the Lombardy regional healthcare service facilitated a rapid increase in hospital bed capacity, the upscaling of SARS-CoV-2 testing capacity, and the achievement of vaccination goals to address the COVID-19 emergency. Therefore, alongside a robust and adequately funded public healthcare service, the private sector serves as an asset to enhance the resilience of healthcare systems, in line with WHO indications.